Five ways to make your one-on-one meetings more effective : failing to use time with direct reports in a meaningful way, or, worse, skipping these meetings altogether, can lead to higher attrition and drag down organizational goals - Wisdom, Jessica (MIT Sloan Management Review, 2023)
Weekly check-in meetings between managers and their teams or direct reports can feel like a waste of time without an agenda or a shared set of goals and expectations, but they are key opportunities to build trusting manager-employee relationships. The author shares five science-backed steps to help managers structure their one-on-ones with direct reports and team members, along with five key questions managers can focus on when meeting with a direct report.